Presencia del Autor en el Narrador y el Protagonista de El recurso del metodo, de Alejo Carpentier - Aparicio, Yannelys (Neophilologus, 2023)
Alejo Carpentier is a writer who handles a huge volume of intellectual and cultural nature, due to his exquisite competence in subjects as different as music, architecture, history, philosophy, anthropology, art and literature. Thanks to his polished education from childhood and the endless curiosity and capacity to wonder about the cultural phenomena that affect the transatlantic field, his novels are constantly nourished by intertextualities, quotes, reflections on history, art or music, which are combined adequately with its critical, social, political and formal purposes. But this erudition, typical of the presence of the baroque in his work, also causes the author to intrude on many occasions in the narrative, undoubtedly marking his presence in some characters, almost always protagonists, and in the narrators of his works, for what the distance between author and narrator or characters is sometimes narrowed to almost imperceptible limits. This occurs especially when certain historical figures combine negative attitudes that are the object of criticism, with admirable characteristics, related to knowledge, culture and sensitivity for art, such as the dictator of El recurso del metodo, who is rejected for his tyrannical tendencies while being admired for his musical, historical and artistic knowledge.
Keywords: Alejo Carpentier; El recurso del método; Latin American Dictatorships; intertextuality; post-ofcial history; WOS; Scopus